ANALISIS KEMAMPUAN SEKUESTRASI DAN PENYIMPANAN KARBON HUTAN MANGROVE DI DESA PEJARAKAN, KABUPATEN BULELENG, BALI - Armyn Atlanta Putra; Rudianto; Citra Satrya Utama Dewi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Mangroves have a major role as carbon absorption and stock. However, this potential cannot be maximized, due to the high level of mangrove damage. The research question is the extent of the ability of mangroves to absorb carbon dioxide (CO2) and store it in the form of biomass. The purpose of this study was to determine the absorption ability and carbon stock of various types of mangove. The research location was chosen in Pejarakan village, Buleleng Regency, Bali Province, Indonesia as a case study. The method used is non-destructive to obtain diameter data at the height of mangrove trees, by collecting garbage and sediment samples manually on the floor of mangrove forests and to motivate the Government and local communities to restore mangrove forests. The results showed that the high density types of Sonneratia alba turned out to have the ability to absorb and store carbon, compared to other mangrove species. The results showed that S. alba is estimated to have the ability to absorb 57.60 tons of CO2 ha-1 which is equivalent to 15.71 tons C ha-1. While the lowest value is the Osbornia octodonta with the lowest density value. S. alba's ability to store carbon is 5.56 tons of CO2 ha-1 or equivalent to 1.52 tons C ha-1. The conclusion is that S. alba has the highest ability to absorb and store carbon.